2012
DOI: 10.3168/jds.2011-4606
|View full text |Cite
|
Sign up to set email alerts
|

Variation among individual dairy cows in methane measurements made on farm during milking

Abstract: The objective of this study was to quantify on-farm variation between and within cows in methane emissions measured during milking, and to determine which factors are related to this variation. Methane emission rate during milking (MERm) was recorded at milking using methane analyzers installed in automatic (robotic) milking stations for 215 cows over a period of 5 mo. Between-cow variation in MERm (mean 2.07, SD 0.629 g/min), was greater than within-cow variation and was related to variation in body weight, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
99
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 18 publications
21
99
1
4
Order By: Relevance
“…Several studies have worked on developing methods for large-scale phenotyping of individual CH 4 measurements (Garnsworthy et al 2012;Lassen et al 2012). These methods focus on CH 4 recordings while cows are being milked in automatic milking systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have worked on developing methods for large-scale phenotyping of individual CH 4 measurements (Garnsworthy et al 2012;Lassen et al 2012). These methods focus on CH 4 recordings while cows are being milked in automatic milking systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the feed intake and milk yield data obtained in this type of study may not fully represent the milk production potential of cows over a full lactation. There is evidence indicating that daily CH 4 emission rates (g/day) of dairy cows varied considerably during lactation, but followed the variation curves of feed intake and milk production (Garnsworthy et al, 2012). Daily CH 4 emission rates also vary among cows on commercial farms (Bell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dietary treatments on methane emissions was presented by Garnsworthy et al (2011) and showed that when cows were fed on treatment HMD significantly (P<0.05) higher values were obtained for MERm (+5%, P=0.042) and MERmDM (+20%, P<0.001). A total of 58 milk fatty acids were identified, and 40 of them differed significantly (P<0.05) between C and HMD.…”
Section: Resultsmentioning
confidence: 99%
“…A dairy concentrate was also fed during milking (1.6 kg/d plus 0.16 kg/kg milk yield above 23 kg/d). Methane concentrations in exhaled air were measured at each milking and eructation data (peak area and frequency) were used to calculate individual daily means for methane emission rate during milking (MERm), as described by Garnsworthy et al (2011). Milk samples were collected on the last day of each experimental period and analysed for fatty acid profile by gas chromatography (GC).…”
Section: Methodsmentioning
confidence: 99%